Acyclic halogen and hydrogen bonding diquat-containing receptors for the electrochemical sensing of anions. (25th September 2016) - Mullaney, Benjamin R.; Cunningham, Matthew J.; Davis, Jason J.; Beer, Paul D.
Graphical abstract: The first examples of halogen and hydrogen bonding anion receptors containing the redox-active diquat motif, and their anion recognition and electrochemical sensing properties are described. The halogen bonding host displayed the strongest halide binding affinities in competitive solvents, and the redox-active diquat group is shown to be an effective electrochemical sensing probe for halides. Abstract: The first examples of halogen and hydrogen bonding anion receptors containing the redox-active dicationic diquat motif and their anion recognition and electrochemical sensing properties are described. The acyclic receptors demonstrated strong binding affinities for halide anions in competitive solvents, with the most potent anion binding behaviour observed for the halogen bonding analogue. The redox-active diquat group is shown to be an effective electrochemical sensing probe, undergoing significant cathodic perturbations of the diquat 2+ /diquat + redox couple upon the addition of halides.